Regulation of apoptotic and growth inhibitory activities of C/EBPα in different cell lines - Wang, Guo-Li (2008)
C/EBPα is expressed in many tissues and inhibits cell growth. In this paper, we have examined mechanisms which regulate activities of C/EBPα in cell lines derived from different tissues. We found that C/EBPα possesses strong pro-apoptotic activity in NIH3T3 cells, while this activity is not detected in 3T3-L1, Hep3B2 and HEK293 cells. Micro array data show that C/EBPα activates many genes of apoptosis signaling in NIH 3T3 cells. One of these genes, ARL6IP5, is a direct target of C/EBPα and is a key mediator of the apoptosis. Using C/EBPα mutants which do not cause cell death; we have found that C/EBPα does not arrest proliferation of NIH3T3 cells. The lack of growth arrest in NIH3T3 cells correlates with the inhibition of p16INK4 and with low levels of cyclin D3. The limited growth inhibitory activity of C/EBPα is also observed in Hep3B2 cells which express low levels of cyclin D3. Elevation of cyclin D3 restores growth inhibitory activity of C/EBPα in NIH3T3 and in Hep3B2 cells. These data show that apoptotic and growth inhibitory activities of C/EBPα are differentially regulated in different cells and that cooperation of cyclin D3 and C/EBPα is required for the inhibition of proliferation.